Role of postoperative chemoradiotherapy in head and neck cancer without positive margins or extracapsular extension: a propensity score-matching analysis - Liu, Zhi-Qiao; OuYang, Pu-Yun; Zhang, Bao-Yu; Chen, En-Ni; Xiao, Su-Ming; Yang, Shan-Shan; Yang, Zhong-Yuan; Xie, Fang-Yun (Radiation oncology (London, England), 2022)
The aim of this work was to determine whether patients with intermediate-risk head and neck squamous cell carcinoma (HNSCC) can benefit from postoperative chemoradiotherapy (POCRT). Patients without extracapsular extension (ECE) or positive margins (PMs) who received POCRT or postoperative radiotherapy (PORT) at our center were retrospectively (December 2009 to October 2018) included for analysis, in particular, using a propensity score-matching method. After matching, 264 patients were enrolled, including 142 (41.2%) patients with pT3-4, 136 (38.3%) patients with pN2-3, 68 (21.1%) patients with perineural invasion, and 45 (12.8%) patients with lymphatic/vascular space invasion. With a median follow-up of 52 months, 3-year overall survival (OS), locoregional relapse-free survival (LRFS), distant metastasis-free survival (DMFS) and disease-free survival (DFS) rates were 72.4%, 79.3%, 83.5% and 62.5%, respectively. pN2-3 was an independent risk factor for OS (p < 0.001), DFS (p < 0.001), LRFS (p < 0.001) and DMFS (p = 0.002), while pT3-4 was a poor prognostic factor for DMFS (p = 0.005). Overall, patients receiving POCRT had no significant differences from those receiving PORT in OS (p = 0.062), DFS (p = 0.288), LRFS (p = 0.076) or DMFS (p = 0.692). But notably, patients with pN2-3 achieved better outcomes from POCRT than PORT in 3-year OS (p = 0.050, 63.9% vs. 47.9%) and LRFS (p = 0.019, 74.6% vs. 54.9%). And patients with pT3-4 also had higher 3-year LRFS (p = 0.014, 88.5% vs. 69.1%) if receiving POCRT. Among all intermediate-risk pathological features, pN2-3 and pT3-4 were independent unfavorable prognostic factors for patients with HNSCC without PMs or ECE. POCRT can improve the survival outcomes of patients with pN2-3 or pT3-4.